2000
DOI: 10.1067/mjw.2000.109082
|View full text |Cite
|
Sign up to set email alerts
|

A nursing assessment tool for adults with fecal incontinence

Abstract: Fecal incontinence affects slightly more than 1% of community-dwelling adults. This article describes an assessment format, with a research basis when available, that has been developed in a specialist nursing clinic in the United Kingdom. The focus is on how to obtain the most useful information from the patient to plan appropriate nursing interventions. A subsequent article will describe the biofeedback program developed as part of a package of care to meet individual needs of persons with fecal incontinence. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…Because incontinence is associated with stigma and reluctance in reporting, inquiring about incontinence when performing a health history or assessment of community-living patients has been recommended. 15,16 The findings of this study support that inquiring about and assessing for IAD in community-living patients with incontinence is important as well. Supplementing patient teaching about using a mirror for assessing for IAD in the perineal area with written materials with diagrams or practice in the clinic setting may be beneficial.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Because incontinence is associated with stigma and reluctance in reporting, inquiring about incontinence when performing a health history or assessment of community-living patients has been recommended. 15,16 The findings of this study support that inquiring about and assessing for IAD in community-living patients with incontinence is important as well. Supplementing patient teaching about using a mirror for assessing for IAD in the perineal area with written materials with diagrams or practice in the clinic setting may be beneficial.…”
Section: Discussionsupporting
confidence: 71%
“…Of the 98 subjects who assessed their skin for IAD in this study, 45 had a history of IAD 16 and 32 of those (71%) developed IAD during this study. There was no significant difference in the incidence of IAD between men vs women (12% vs 40%, p =.35) and older (≥ 65 years) vs younger subjects (40% vs 37% p =.61).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Norton and Chelvanayagam 30 reported that some women with FI feel socially restricted, and in severe cases, remained in the home due to FI. More women than men in our study expressed the negative impact of FI on social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 outlines the evidence-based assessment and treatment protocol. 1,9,16,[22][23][24][25][26] The intervention consisted of a 1-off assessment by a nurse 22 leading to (1) targeted patient and carer education; (2) provision of booklet; and (3) diagnostic summary and treatment recommendations sent to the patient's general practitioner (GP), and ward physician if in hospital. The nonspecialist study nurse received simple practice-based training in bowel management.…”
Section: Interventionmentioning
confidence: 99%